PARTICIPATION OF COORDINATION SKILLS ON THE LEVEL OF SWIMMING CAPABILITY OF PRESCHOOL CHILDREN (Fiep Bulletin - online, 2014)
In our paper we present the partial results, which aim was to extend the knowledge about the participation of coordination skills on swimming capability of children at preschool-age. We assessed the present level of coordination skills of preschool-age children at the start and at the end of the swimming course using test “Obstacle course in water”, Jump into water, Level of diving, Orientation under water, Floating, Swimming across distance Crawl kicking with board. The level of the swimming capabilities was evaluated by swimming across distances. Based on the tests results, we can determine a significant correlation between the evaluated indicators. After the completion of the swimming course, children with higher levels of coordination abilities demonstrated significantly higher levels of swimming competence. The used tests were adapted to children at preschool age and it is possible to recommend them for testing of coordination skills in the water in this age category.
Keywords: Swimming; swimming capability; dynamic balance; obstacle course in water; preschool-age